Head shot - Jardine, Quintin, 1945- (Bob Skinner ;, 2003)
Deputy Chief Constable Bob Skinner has witnessed the aftermath of murder countless times.Yet nothing could have prepared him for identifying the strangled bodies of his wife's beloved parents, killed at their lakeside cabin in New York State.Driven by cold rage, Skinner quickly muscles in on the investigation, and soon he's found links with three other cases where the killing is too professional to be the result of a burglary gone wrong.But can he penetrate the multiple layers of intrigue to unearth the killer?